Projeto de um framework para visualização e controle de simulações distribuídas em diferentes plataformas de software e hardware - Iwasaki, Fábio Minoru (2008)
Computer simulation can be used to assess future risks and to support decision making and can be modeled either for quick runs to predict the state of a real-world system or for indeterminate runtime to allow human interaction in a virtual environment for training. To facilitate the modeling and implementation of those simulations, many commercial software suites are available, but proprietary technologies are limited when there is the need to reuse a particular implementation together with other solutions. Faced with the need for interoperability, the High Level Architecture (HLA) standard defines a communication infrastructure for data sharing and synchronization among distributed simulation models. Using the HLA as its basis, this work defines a framework to generate an application for simulation control and management using tridimensional graphics for visualization through the Extensible 3D (X3D) standard. The X3D specifies a runtime environment for 3D content presentation and defines a language and a set of components to describe that content. By using the HLA and X3D standards integrated into technologies such as Web services, this framework provides a solution to visualization and control of distributed simulations in different software and hardware platforms.